Foundations of minority communities: Resident Koreans in Japan - David Rands (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper discusses the development of Korean communities in Japan from their origins in the late nineteenth century through their stabilization following the Second World War. Approaching the developing communities from a spatial perspective, the chapter compares Tokyo and Osaka and shows the connections between the urban environment and development of migrant communities. The chapter shows that the conditions of urban environments are specific to each city and that those distinctions constitute the primary factors in determining the success or failure in the development of migrant communities.
Keywords: R1; J7; 330; zainichi; minorities; Osaka; Tokyo; Tsuruhashi